Stock return response to changes in msci standard and small cap index composition for Turkey - AVCI, EMİN; ÇİNKO, MURAT; ÖNER, MEHTAP; AYBARS, ASLI (My University, 2023)
The effect of index reconstitution on stock return and volume have been one of the controversial subjects in finance. Although, there are several researches, which are analyzing the domestic stock market index effect on stocks, a few studies focused on the effects of an international index. By the use of event study methodology, this paper analyzes the price effect of changes in constituents of two MSCI indexes (Standard Index and Small Cap Index) for Turkish companies as of announcement and effective dates. Overall, there are four analyses; namely, addition to Small Cap Index with respect to announcement (effective) day, deletion from Small Cap Index with respect to announcement (effective) day, addition to Standard Index with respect to announcement (effective) day, and deletion from Standard Index with respect to announcement (effective) day. The findings of the study present that index effect appears or disappears, resting upon the index, on which index reconstitution is being analyzed. Moreover, existence of the index effect is also subject to event day definition, which may be either announcement date or effective date of the index event. Significant index effect strongly exists for the additions to MSCI Standard Index around announcement date, while deletions have significant, but weaker, effect around the effective date. No significant index effect has been found for deletions around announcement date. Index effect is also documented around announcement and effective dates for MSCI Small Cap Index additions; however, such effect is quite stronger for deletions from MSCI Small Cap Index around the announcement dates.

Endeks kapsam değişimlerinin hisse getirisi ve hacmi üzerindeki etkisi finans alanında tartışılan konulardan biri olmuştur. Birçok çalışma yurtiçi endeks değişimlerinin hisse senetleri üzerindeki etkisini analiz ederken, uluslararası endeks değişimlerinin etkisini inceleyen çalışmalar daha azdır. Bu çalışma, iki MSCI endeksindeki (Standard Index and Small Cap Index) Türk firmalarının endeksten çıkarılması ve endekse eklenmesi ile ilgili değişimlerin hisse fiyatını nasıl etkileyeceğini vaka analizi yöntemi kullanarak incelemektedir. Değişimlerin hem ilan edildiği hem de gerçekleştiği tarih dikkate alınarak dört analiz yapılmıştır. Bu analizler ilan ve gerçekleşme günlerini dikkate alarak Small Cap endeksine eklenmeyi ve endeksinden çıkarılmayı, ayrıca Standard endekse eklenmeyi ve endeksten çıkarılmayı içermektedir. Çalışmanın bulguları, değişimin analiz edildiği endekse bağlı olarak endeks etkisinin ortaya çıkabildiğini ya da ortadan yok olabildiğini göstermiştir. Buna ek olarak, endeks etkisinin varlığının ilan günü veya yürürlük günü gibi olay günü tanımlarından etkilendiği gözlemlenmiştir. İlan günü civarında MSCI Standart Endeksine yapılan eklemeler için anlamlı ve güçlü bir endeks etkisi bulunurken, endeksten çıkarmalarınyürürlük günü civarında anlamlı ancak daha zayıf bir etkisi vardır. İlan günü civarındaki çıkarmalar için ise anlamlı bir endeks etkisi bulunmamıştır. MSCI Small Cap endeks eklemelerinin ilan ve yürürlük günleri civarında da endeks etkisi bulunmuştur; ancak bu etki, ilan günü civarında endeks kapsamından çıkarmalarda oldukça güçlüdür
Hisse senedi getirisinin ‘MSCI standard’ ve ‘small cap’ endeks kapsam değişimine tepkisi: Türkiye örneği
Keywords: Endeks Etkisi; MSCI Endeksi; Endeks Kapsam Değişimi; Vaka Analizi; Index Effect; MSCI Index; Index Reconstitution; Event Study